Sejarah Sistem Peradilan Pidana Anak Di Indonesia - Fernando, Yory (Lembaga Penelitian dan Pendidikan (LPP) Mandala, 2020)
As national assets and who are also legal subjects, children have a strategic role in the life of the nation and state. Because of this strategic role, every problem regarding children cannot be underestimated. The Convention on the Rights of the Child (CRC) is proof that the international community guarantees children’s rights. In Indonesia, the rights of the child have been stated in Act No. 11/2012 concerning the Juvenile Criminal Justice System. However, these regulations do not just appear, it needs a long enough process to form regulations that guarantee the interests and rights of a child. The history of the formation of the Child Criminal Justice System is divided into 3 periods, namely; The period before the birth of Law Number 3 of 1997, the period after the birth of Act No. 3/1997, and the period after the birth of Act No. 11/2012. It can be concluded from these three periods that before the birth of Act No. 11/2012, there have been several regulations governing the interests of children but their implementation is far from perfect, and the birth of Act No. 11/2012 is a milestone that has brought major changes to ensuring children's rights in Indonesia.